Pelaksanaan Program Kemitraan Pola Perusahaan Inti Rakyat (PIR) Pemeliharan Broiler dan Implikasinya Terhadap Pendapatan Peternak di Kota Pekanbaru - Asdi Agustar (Universitas Andalas, 2007)
The aims of the present study were to evaluate the biological and economic performances of broiler raising between farmers as member and non members of nucleus-plasma scheme (PIR) in Pekanbaru city. Thirty broiler farmers from each member and non member of PIR were visited and interviewed to collect data: mortality rate, body weight gain, production cost and revenues. The data were then calculated to find out: net income and return to equity. Results showed that the biological and economical performances in term of mortality, daily weight gain and profitabilities of broiler raised farmer of member of PIR were found better than that of raised by the PIR members. These indicated that the program of nucleus-plasma scheme gave no improvement in farming practices and profitability for the farmer in Pekanbaru city.